Musical performance as a perspective of Schenker’s theoretical-analytical proposa (Orfeu, 2021)
Performance experience is the perspective of this article’s discourse, which starts from the contextualization of Schenker’s first two phases, based on the publications Die Kunst des Vortrags (“The art of performance”), Der Tonwille (“Contextual Music Analysis”) and Das Meisterwerke in der Musik (“The masterpieces of music”). Contextualized by a discussion about his theoretical-analytical influence and conception of performance in studies related to the Analysis and Musical Performance subarea, it identifies links between structure and expressiveness in Schenker and neo-schenkerian theorists’ analyses. It demonstrates how the perception of the interlocution between metrical events and voice leading served as basis for sound modelling issues in studies elaborated by Charles Burkhart, Steve Larson, Carl Schachter and David Beach. This work does not fail to consider the strongly prescriptive aspects present in these proposals, but seeks to study them from current research perspectives.
Keywords: Musical parameters; Multilevel graph; Musical Analysis and Performance; Heinrich Schenker; Neo-Shenkerian